The book of Koheleth commonly called Ecclesiastes ; considered in relation to modern criticism,and to the doctrines of modern pessimism, with a critical and grammatical commentary and revised translation. - Wright, Charles Henry Hamlton (London, UK Hodder and Stoughton, 1883)
Includes bibliographical references.
Keywords: Bible. O.T. Ecclesiastes -- commentaries